Respuesta :
Answer:
-16
Step-by-step explanation:
Here, we have to use the general term to find the third term.
Given,
nth term is
b(n)=b(n-1)-7
Using n=2, we get
b(2)=b(2-1)-7
=b(1)-7
we are given b(1)=-2
So, b(2)=-2-7
=-9
Now, using n=3 in the nth term we get
b(3)=b(3-1)-7
=b(2)-7
using b(2)=-9 from above we get
b(3)=-9-7
=-16
So, the 3rd term is -16
Hey there!!
Given is an recursive formula :-
... b(n) = b(n-1) - 7
In this equation, 'n' is the number of the term we will need to find and '-7' is the common difference.
... b(1) = -2
We get to know that the first term is -2.
Now, we will find the 2nd term :-
... b(2) = b(2-1) - 7
... b(2) = b(1) - 7
We know b(1) is -2.
... b(2) = -2-7
... b(2) = -9
The second terms is -9 b(2) = -9
Now, let's find the third term :-
... b(3) = b(3-1) - 7
... b(3) = b(2) - 7
We know b(2) is -9
... b(3) = -9-7
... b(3) = -16
The third terms is -16.
Hence, the third term and the answer is -16.
Hope my answer helps!!